In the Court of the Pear King : French Culture and the Rise of Realism - Petrey, Sandy (Book collections on Project MUSE., 2005)
Sandy Petrey explores the factors accounting for such consequential innovations in so short a time, so restricted a space. In Petrey's view, these disparate events betoken a common recognition of society's capacity to make and unmake what it recognizes as real."--Jacket.